A implementação dos bondes elétricos na cidade de Belém: o liberalismo higienista da elite belenense (1900-1909) - SILVA, Rafael Baía da (2023)
At the beginning of the twentieth century, the elite of Belém experienced transformations resulting from the peak of rubber exploration. This article aims to analyze how the implementation of electric trams modified the circulation of people in the city of Belém and the repercussions of this urban development, which prioritized the commercial center at the expense of areas of areas inhabited by the lower classes of the city. In addition to this objective, we seek to examine the process of hygienization that characterized this modernization context. Furthermore, discourse analysis will assist us in understanding the political and economic aspects that guided the proposals for the city’s modernization presented by Antônio Lemos from 1900 to 1909 and consulted the collection of newspapers from Belém at the Brazilian Digital newspaper library for the same period.